Up-conversion luminescence of Er 3 +-doped glass ceramics containing ß-NaGdF 4 nanocrystals for silicon solar cells - Xin, F.; Zhao, S.; Huang, L.; Deng, D.; Jia, Guohua; Wang, H.; Xu, S. (Elsevier BV, 2012)
A new Er 3 + doped oxyfluoride borosilicate glass ceramics was developed by controlling crystallization of the quenched glass. The hexagonal NaGdF 4 nanocrystals were precipitated in the glass matrix, which was confirmed by the X-ray diffraction and TEM results. Notable enhancement of upconversion emission was observed in the Er 3 + doped glass ceramics and attributed to the enrichment of Er 3 + into NaGdF 4 nanocrystals. With the increasing of Er 3 + content, the upconversion emission density ration from green to red light greatly changed in the glass ceramics. This material may be used as a potential material for the silicon solar cells. © 2012 Elsevier B.V. All rights reserved.